Artificial β-propeller protein-based hydrolases. Issue 60 (19th July 2019) - Clarke, David E.; Noguchi, Hiroki; Gryspeerdt, Jean-Louis A. G.; De Feyter, Steven; Voet, Arnout R. D.
Abstract : We investigated symmetrical β-propeller protein scaffolds as artificial hydrolases and discovered their catalytic mechanism to be centred around a threonine–histidine dyad. Abstract : We developed an artificial hydrolase based on the symmetrical Pizza6 β-propeller protein for the metal-free hydrolysis of 4-nitrophenyl acetate and butyrate. Through site-specific mutagenesis and crystallisation studies, the catalytic mechanism was investigated and found to be dependent on a threonine–histidine dyad. The mutant with additional histidine residues generated the highest k cat values, forming a His–His–Thr triad and matched previously reported metalloenzymes. The highly symmetrical β-propeller artificial enzymes and their protein–metal complexes have potential to be utilised in bioinorganic and supramolecular chemistry, as well as being developed further into 2D/3D catalytic materials.